Generation and evolution of stable noise-like pulse with varying dispersion in figure-of-eight erbium-doped fiber laser - Maad, Hikmat; Mohd Yusoff, Norita; Ahmad Anas, Siti Barirah; Mokhtar, Makhfudzah; Zan, Zuraidah; Mahdi, Mohd Adzir (Academic Press Inc., 2024)
A stable noise-like pulse (NLP) in a figure-of-eight nonlinear optical loop mirror (NOLM) erbium-doped fiber (EDF) laser is proposed and demonstrated. The work experimentally investigated the effect of dispersion in the generation and evolution of the NLP by varying the length of single mode fiber (SMF) in the NOLM bidirectional loop (bi-loop). The lengths are 5 m, 10 m, 15.2 m, 20.2 m, 25.9 m, 50.1 m, 76.9 m, and 103.7 m with their net cavity dispersion of −0.275 ps2, −0.386 ps2, −0.500 ps2, −0.611 ps2, −0.737 ps2, −1.269 ps2, −1.859 ps2, and −2.447 ps2, respectively. The stability of the NLP was first evaluated by analyzing a temporal trace of the spike and its pedestal from an autocorrelator, followed by a long-term stability test of 350 min. The work demonstrated a stable NLP was obtained at the SMF length of 25.9 m at a threshold pump of 260.6 mW. At the maximum pump power of 344.7 mW, the pulse energy of 7 nJ was obtained with the highest output power of 29.77 mW. The respective spike and pedestal widths were demonstrated to be at 236.87 fs and 65.74 ps, respectively. The net cavity dispersion was −0.737 ps2 with 49.82 m total cavity length, and the corresponding repetition rate was 4.25 MHz. This work presents the importance of dispersion management of the NOLM to generate a stable NLP at low threshold power.